2009
DOI: 10.1111/j.1547-5069.2009.01288.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Presence During Resuscitation: Canadian Critical Care Nurses’ Perspectives

Abstract: The results of this study provide information for practicing clinicians, educators, and administrators regarding the decision-making processes nurses use when considerations of bringing family members to the bedside during resuscitative events are evoked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
51
0
37

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(94 citation statements)
references
References 37 publications
6
51
0
37
Order By: Relevance
“…Similarly, perceived benefits of family presence in our study aligned closely with studies of patients, patients' families, and health professionals. 9,11,15,16,[18][19][20][21]37,42 No new benefits emerged from our data, confirming a growing and strong consensus about benefits.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Similarly, perceived benefits of family presence in our study aligned closely with studies of patients, patients' families, and health professionals. 9,11,15,16,[18][19][20][21]37,42 No new benefits emerged from our data, confirming a growing and strong consensus about benefits.…”
Section: Discussionsupporting
confidence: 69%
“…2,9,[14][15][16][17] Research with health professionals similarly suggests that family presence during resuscitation and invasive procedures helps families grasp the severity of life-threatening events, facilitates communication, supports grieving, allows families to see the efforts of the care team, and reduces litigation risk. 9,15,16,[18][19][20][21] Health professionals also perceive disadvantages, including performance anxiety of resuscitation teams, family disruptions of care, deleterious effects on family, compromised patient confidentiality, increased litigation risk, and family's desires to prolong futile resuscitation. 9,[18][19][20][22][23][24][25] Research findings have not supported the disadvantages perceived by health professionals 17,19,26,27 ; therefore, major health organizations now encourage family presence during resuscitation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in different countries -France, 8 Canada, 10 Ireland 11 and the United States 12 -showed that professionals working in emergency units, although they recognized the existence of many challenges for the implementation of the FCC, perceived it as a driver of qualification of care of grave patients and humanized the assistance. 8,[10][11][12] In the Brazilian context, FCC is still incipient, has not been implemented in the health services nor discussed in vocational training.…”
Section: Introductionmentioning
confidence: 99%
“…8,[10][11][12] In the Brazilian context, FCC is still incipient, has not been implemented in the health services nor discussed in vocational training. This brings up the following question: What is the perception that Brazilian doctors and nurses working in emergency units have about the FCC?…”
Section: Introductionmentioning
confidence: 99%